Nintedanib Inhibits Wnt3a-Induced Myofibroblast Activation by Suppressing the Src/β-Catenin Pathway - Li, Xiaohe; Liu, Xiaowei; Deng, Ruxia; Gao, Shaoyan; Yu, Haiyan; Huang, Kai; Jiang, Qiuyan; Liu, Rui; Li, Xiaoping; Zhang, Liang; Zhou, Honggang; Yang, Cheng (Frontiers in Pharmacology, 2020)
IPF is an interstitial lung disease characterized by epithelial cell damage, myofibroblast activation, and collagen deposition. Multiple studies documented that Wnt/β-catenin pathway is aberrant activated in IPF and plays a vital role in myofibroblast differentiation and activation. Kinases such as Src initiate Wnt/β-catenin signaling by phosphorylating β-catenin at tyrosine residues, which facilitates β-catenin the ability to accumulate in the nucleus and promote fibrosis progress. Nintedanib has been approved for the treatment of idiopathic pulmonary fibrosis as a multitargeted tyrosine kinase inhibitor. Since Nintedanib has been demonstrated to directly block Src, whether Nintedanib attenuates pulmonary fibrosis through regulating Wnt/β-catenin pathway remains unclear. In this study, we found that Nintedanib attenuated myofibroblast activation through inhibiting the expression of Wnt signaling downstream genes such as Cyclin D1, Wisp1 and S100a4. Further studies showed that Nintedanib inhibited Wnt3a-induced β-catenin nuclear translocation through suppressing Src kinase activation and β-catenin Y654 phosphorylation. Besides, Src konckdown fibroblasts exhibited similar phenotype with that of the Nintedanib treatment group, and the inhibition effects of Nintedanib was consistent with the Src kinase inhibitor Saracatinib. In summary, our study shows that Nintedanib exhibits anti-fibrosis effect partly via inhibiting the Src/β-catenin pathway.